Map of the country around Esquimalt Harbour - Pemberton, J. Despard (Joseph Despard), 1821-1893 (1852)
Deadman's river, The Portage Inlet, Beacon on Mt. Douglas, Knockan, Boundary of original Fur trade Reserve, Victoria Harbour, Macaulay's, Beacon on Beacon Hill, Bank 300 ft high, Mill Mt., Mt Seymour, Saanich Inlet, Lading Peak, depth 70 80 feet, Metchosin River